Customer Loyalty: A Systematic Literature Review - Syerli Primasari; Vidyarini Dwita (Journal of Indonesian Management, 2025)
The purpose of this article is to identify and analyze several references related to the keyword "customer loyalty." Utilizing Harzing's Publish or Perish, a systematic literature review was conducted for this study using the Scopus database. Employing the SPAR-4-SLR protocol, data analysis was performed using Microsoft Excel, Mendeley, and VOS Viewer to ensure transparency and replicability. The findings of this study identified 82 primary articles indexed in Scopus Q1 based on the Scimago Journal Ranking (SJR). The study also discovered seven knowledge clusters supporting research on customer loyalty, with a total link strength of 214. VOS Viewer visualization revealed that "Customer Loyalty" is significantly prominent and is associated with the phrase "Customer Satisfaction," demonstrating a clear relationship. This study has several limitations, such as constraints in database access restricted to Scopus. Therefore, future research is recommended to expand data collection by incorporating additional sources such as Emerald, SpringerLink, Science Direct, EBSCO, Google Scholar and non-Q journals like Web of Science.